Negative electrode current collector for lithium ion secondary battery, and negative electrode for lithium ion secondary battery
The laminate structure with a nickel-containing second metal layer, designed to reduce nickel content along its thickness, addresses peeling issues in negative electrode current collectors, improving durability and tensile strength by minimizing hardness differences.
Patent Information
- Application Number
- JP2022577039
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-01-20
- Filing Date
- 2021-12-16
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-12-16
AI Technical Summary
Conventional negative electrode current collectors for lithium ion secondary batteries experience peeling of the second metal layer due to differences in hardness and elastic modulus between the first and second metal layers, leading to deformation and potential short circuits.
A laminate structure with a second metal layer containing nickel, where the nickel content decreases along the thickness direction, reducing the elastic modulus gradient and minimizing the difference in hardness between layers, thereby preventing peeling.
The laminate structure effectively suppresses peeling of the second metal layer from the first, enhancing the durability and tensile strength of the negative electrode current collector, reducing deformation and potential short circuits.
Smart Images

Figure 0007607679000002 
Figure 0007607679000003 
Figure 0007607679000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate, a negative electrode current collector for a lithium ion secondary battery, and a negative electrode for a lithium ion secondary battery. [Background technology]
[0002] A negative electrode current collector for a lithium ion secondary battery is subjected to repeated loads (compressive stress and tensile stress) due to the volume of the negative electrode active material layer laminated on the negative electrode current collector fluctuating with charging and discharging. The deformation of the negative electrode current collector due to this load causes deformation of the battery body or short circuit between the electrodes. Therefore, the negative electrode current collector is required to have durability against the load. For example, the following Patent Document 1 discloses a negative electrode current collector having a tensile strength, in which an electrode foil containing copper and a hard nickel plating layer are laminated. The following Patent Document 2 discloses a current collector having a sufficient strength to suppress cracking and tearing, in which a first metal layer made of copper and a second metal layer made of nickel or a nickel alloy are laminated. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2005-197205 A [Patent Document 2] JP 2019-186134 A Summary of the Invention [Problem to be solved by the invention]
[0004] When the laminate has a first metal layer containing copper and a second metal layer containing nickel and directly laminated on the first metal layer, as in the conventional negative electrode current collector described above, the second metal layer is likely to peel off from the first metal layer due to repeated stress on the laminate. The inventors have found that the peeling of the second metal layer from the first metal layer is caused by the difference in hardness (elastic modulus) between the first metal layer and the second metal layer. For example, the Young's modulus of the second metal layer containing nickel tends to be higher than the Young's modulus of the first metal layer containing copper. In other words, the second metal layer containing nickel is harder than the first metal layer containing copper and is less likely to deform due to stress. In addition, as the content of the additive element other than nickel in the second metal layer increases, the elastic modulus of the second metal layer increases, and the second metal layer tends to become harder.
[0005] An object of one aspect of the present invention is to provide a laminate having a first metal layer containing copper and a second metal layer containing nickel, which suppresses peeling of the second metal layer from the first metal layer, and a negative electrode current collector and a negative electrode for a lithium ion secondary battery which include the laminate. [Means for solving the problem]
[0006] A laminate according to one aspect of the present invention comprises a first metal layer containing copper and a second metal layer containing nickel and laminated directly on the first metal layer, wherein a first surface of the second metal layer is a surface in contact with the first metal layer, a second surface of the second metal layer is a surface opposite to the first surface, a thickness direction of the second metal layer is approximately perpendicular to the first surface and is a direction from the first surface to the second surface, the nickel content of the second metal layer is expressed in units of mass%, and the nickel content of the second metal layer decreases along the thickness direction.
[0007] The second metal layer may further include at least one element selected from the group consisting of phosphorus and tungsten.
[0008] The second metal layer may be composed of a plurality of nickel-containing layers stacked in the thickness direction, and the nickel content of each of the plurality of nickel-containing layers may be different from each other.
[0009] The thickness of the first metal layer is designated T1 and the thickness of the second metal layer is designated T2, where T2 / T1 may be 0.6 or more and 1.0 or less.
[0010] The nickel content of the second metal layer may be highest near the first surface, may decrease stepwise along the thickness, and may be lowest near the second surface.
[0011] The nickel content in the second metal layer may be highest near the first surface, may decrease continuously along the thickness direction, and may be lowest near the second surface.
[0012] A negative electrode current collector for a lithium ion secondary battery according to one aspect of the present invention includes the above laminate.
[0013] A negative electrode for a lithium ion secondary battery according to one aspect of the present invention includes the above-described negative electrode current collector and a negative electrode active material layer containing a negative electrode active material, where the negative electrode active material layer is laminated directly on the second surface of the second metal layer.
[0014] The negative electrode active material may contain silicon. Effect of the Invention
[0015] According to one aspect of the present invention, there is provided a laminate having a first metal layer containing copper and a second metal layer containing nickel, which suppresses peeling of the second metal layer from the first metal layer, and a negative electrode current collector and a negative electrode for a lithium ion secondary battery which include the laminate. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic perspective view of a laminate (negative electrode current collector) according to one embodiment of the present invention, and a negative electrode including the laminate. [Diagram 2] FIG. 2 is a graph showing an example of the distribution of the nickel content in the second metal layer. [Diagram 3]FIG. 3 is a graph showing another example of the distribution of the nickel content in the second metal layer. [Figure 4] FIG. 4 is a schematic diagram showing an outline of the bending test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, preferred embodiments of the present invention will be described with reference to the drawings. In the drawings, the same components are designated by the same reference numerals. The present invention is not limited to the following embodiments.
[0018] The laminate according to this embodiment is a negative electrode current collector for a lithium ion secondary battery. As shown in FIG. 1, the laminate 10 according to this embodiment has a first metal layer 1 and a second metal layer 2. The first metal layer 1 contains copper (Cu). The second metal layer 2 contains nickel (Ni). Since the laminate 10 has not only the first metal layer 1 but also the second metal layer 2 laminated on the first metal layer 1, the laminate 10 can have a higher tensile strength than a conventional current collector consisting of only one metal layer containing Cu. In the case of the laminate 10 shown in FIG. 1, the second metal layer 2 is directly laminated on both surfaces of the first metal layer 1. However, the second metal layer 2 may be directly laminated on only one surface of the first metal layer 1. The first surface S1 of the second metal layer 2 is a surface in contact with the first metal layer 1. The first surface S1 of the second metal layer 2 may be rephrased as an interface between the first metal layer 1 and the second metal layer 2. The second surface S2 of the second metal layer 2 is a back surface of the first surface S1. The thickness direction D of the second metal layer 2 is approximately perpendicular to the first surface S1 and is a direction from the first surface S1 toward the second surface S2.
[0019] 1, the negative electrode 20 for a lithium ion secondary battery according to this embodiment includes a laminate 10 (negative electrode current collector) and a negative electrode active material layer 3. The negative electrode active material layer 3 includes a negative electrode active material. The negative electrode active material layer 3 is laminated directly on the second surface S2 of each second metal layer 2. The lithium-ion secondary battery according to this embodiment may include a negative electrode 20, a positive electrode, a separator, and an electrolyte. The separator and the electrolyte are disposed between the negative electrode 20 and the positive electrode. The electrolyte permeates the separator. The positive electrode may include a positive electrode current collector and a positive electrode active material layer laminated on the positive electrode current collector. For example, the positive electrode current collector may be an aluminum foil or a nickel foil. The positive electrode active material layer contains a positive electrode active material. For example, the positive electrode active material is lithium cobaltate (LiCoO2), lithium nickelate (LiNiO2), lithium manganate (LiMnO2), lithium manganese spinel (LiMn2O4), LiNi x Co y Mn z M a O2 (x + y + z + a = 1, 0 ≦ x < 1, 0 ≦ y < 1, 0 ≦ z < 1, 0 ≦ a < 1, M is one or more elements selected from the group consisting of Al, Mg, Nb, Ti, Cu, Zn, and Cr.), lithium vanadium compound (LiV2O5), olivine-type LiMPO4 (M is one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, and Zr, or VO), lithium titanate (Li4Ti5O 12 ), LiNi x Co y Al z O2 (0.9 < x + y + z < 1.1), one or more compounds selected from the group consisting of polyacetylene, polyaniline, polypyrrole, polythiophene, and polyacene. The positive electrode active material layer may further contain a conductive assistant such as carbon or metal powder. The positive electrode active material layer may further contain a binder (adhesive or resin). The separator may be one or more films (films or laminates) made of a porous polymer having electrical insulation. The electrolyte contains a solvent and an electrolyte (lithium salt). The solvent may be water or an organic solvent. For example, the electrolyte (lithium salt) may be one or more lithium compounds selected from the group consisting of LiPF6, LiClO4, LiBF4, LiCF3SO3, LiCF3CF2SO3, LiC(CF3SO2)3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(CF3CF2CO)2, and LiBOB.
[0020] The unit of the Ni content in the second metal layer 2 is mass %. The Ni content in the second metal layer 2 decreases along the thickness direction D of the second metal layer 2. That is, the Ni content in the second metal layer 2 is highest near the first surface S1, decreases gradually or stepwise from the first surface S1 toward the second surface S2, and is lowest near the second surface S2. The graph in FIG. 2 shows an example of the distribution of the Ni content in the second metal layer 2. The horizontal axis of the graph in FIG. 2 is the distance d from the first surface S1 in the thickness direction D of the second metal layer 2. The vertical axis of the graph in FIG. 2 is the Ni content ([Ni]) at a position in the second metal layer 2 that is a distance d from the first surface S1. As shown in FIG. 2, the Ni content in the second metal layer 2 may decrease continuously (gradually) along the thickness direction D. The distribution of the Ni content in the second metal layer 2 may be represented by a straight line. The distribution of the Ni content in the second metal layer 2 may be represented by a curve.
[0021] The Ni content in the second metal layer 2 decreases along the thickness direction D, thereby making it possible to suppress peeling of the second metal layer 2 from the first metal layer 1. The mechanism by which peeling of the second metal layer 2 from the first metal layer 1 is suppressed is as follows. However, the following mechanism is hypothetical, and the technical scope of the present invention is not limited by the following mechanism.
[0022] The higher the Ni content in the second metal layer 2, the lower the elastic modulus of the second metal layer 2. The lower the elastic modulus of the second metal layer 2, the softer the second metal layer 2 is, and the difference in elastic modulus between the first metal layer 1 and the second metal layer 2 is reduced. Since the content of Ni in the second metal layer 2 decreases along the thickness direction D, the elastic modulus of the second metal layer 2 increases along the thickness direction D. That is, the elastic modulus of the second metal layer 2 is lowest near the first surface S1, increases gradually or stepwise from the first surface S1 toward the second surface S2, and is highest near the second surface S2. Therefore, the difference in the elastic modulus between the first metal layer 1 and the second metal layer 2 decreases along the direction opposite to the thickness direction D and becomes smallest at the first surface S1. That is, the first surface S1 (the first surface S1 that is the softest in the second metal layer 2) having the lowest elastic modulus in the second metal layer 2 contacts the soft first metal layer 1. As a result, the first surface S1 side of the second metal layer 2 is easily deformed to the same extent as the first metal layer 1 in response to the stress that repeatedly acts on the laminate 10 due to the volume change of the negative electrode active material layer 3, and peeling of the second metal layer 2 from the first metal layer 1 is suppressed. Furthermore, the elastic modulus of the second metal layer 2 increases gradually or stepwise along the thickness direction D, dispersing the stress acting on the second metal layer 2 due to the volumetric fluctuation of the negative electrode active material layer 3. As a result, deformation of the second metal layer 2 is suppressed, and peeling of the second metal layer 2 from the first metal layer 1 is also suppressed.
[0023] In order to increase the energy density of a lithium-ion secondary battery, the negative electrode housed in a battery package is wound or folded in a roll shape while being laminated with a separator, an electrolyte, and a positive electrode. Since stress is likely to act on the folded portion of the laminate (negative electrode current collector) constituting the negative electrode, the second metal layer is likely to peel off from the first metal layer at the folded portion of the conventional laminate. On the other hand, according to the present embodiment, peeling of the second metal layer 2 from the first metal layer 1 at the folded portion of the laminate 10 can be suppressed.
[0024] The second metal layer 2 may be composed of a plurality of nickel-containing layers stacked in the thickness direction D, and the Ni content of each of the plurality of nickel-containing layers may be different from each other. In other words, the plurality of nickel-containing layers may be distinguished from each other based on the Ni content. In each nickel-containing layer, the Ni content may be constant. In each nickel-containing layer, the Ni content may decrease along the thickness direction D. The thickness of each nickel-containing layer may be uniform. The number n of nickel-containing layers constituting the second metal layer 2 is an integer of 2 or more and is not particularly limited. For example, any pair of nickel-containing layers constituting the second metal layer 2 is represented as the (k-1)th nickel-containing layer and the kth nickel-containing layer. k is any integer of 2 or more and n or less. The kth nickel-containing layer is directly stacked on the (k-1)th nickel-containing layer in the thickness direction D of the second metal layer 2. When k is 2, the (k-1)th nickel-containing layer (i.e., the first nickel-containing layer) is directly stacked on the first metal layer 1. The distance between the first metal layer 1 and the k-th nickel-containing layer is greater than the distance between the first metal layer 1 and the (k-1)th nickel-containing layer, and the Ni content in the k-th nickel-containing layer is lower than the Ni content in the (k-1)th nickel-containing layer.
[0025] For example, when the number n of nickel-containing layers constituting the second metal layer 2 is 3, the second metal layer 2 is composed of a first nickel-containing layer, a second nickel-containing layer, and a third nickel-containing layer. The first nickel-containing layer is directly laminated on the first metal layer 1, the second nickel-containing layer is directly laminated on the first nickel-containing layer, and the third nickel-containing layer is directly laminated on the second nickel-containing layer. The graph in FIG. 3 shows the distribution of the Ni content in the second metal layer 2 when n is 3. The horizontal axis of the graph in FIG. 3 is the same as the horizontal axis of the graph in FIG. 2, and the vertical axis of the graph in FIG. 3 is the same as the vertical axis of the graph in FIG. 2. As shown in FIG. 3, the Ni content in the third nickel-containing layer L3 is lower than the Ni content in the second nickel-containing layer L2, and the Ni content in the second nickel-containing layer L2 is lower than the Ni content in the first nickel-containing layer L1. The Ni content may be constant within each of the first nickel-containing layer L1, the second nickel-containing layer L2, and the third nickel-containing layer L3, and the Ni content in the second metal layer 2 may decrease stepwise along the thickness direction D.
[0026] Ni may be the main component of the second metal layer 2. In other words, when the second metal layer 2 contains a plurality of elements, the Ni content may be the highest. The Ni content in the second metal layer 2 may be, for example, 60% by mass or more and less than 100% by mass, or 60% by mass or more and 99% by mass or less. When the second metal layer 2 contains three or more elements, the Ni content in the second metal layer 2 may be less than 50% by mass. A part of the second metal layer 2 may be simple Ni. At least a part or the whole of the second metal layer 2 may be an alloy containing Ni, or an intermetallic compound containing Ni. When the Ni content in the second metal layer 2 is within the above range, peeling of the second metal layer 2 from the first metal layer 1 is easily suppressed.
[0027] The Ni content in the second metal layer 2 is maximum in the vicinity of the first surface S1 of the second metal layer 2. The maximum value of the Ni content in the second metal layer 2 is [Ni] MAX The Ni content in the second metal layer 2 is the smallest in the vicinity of the second surface S2 of the second metal layer 2. The minimum value of the Ni content in the second metal layer 2 is [Ni]MIN Δ[Ni] is expressed as [Ni] MAX -[Ni] MIN is defined as follows. Δ[Ni] may be 4 mass% or more and 18 mass% or less, or 6 mass% or more and 12 mass% or less. When Δ[Ni] is within the above range, peeling of the second metal layer 2 from the first metal layer 1 is easily suppressed.
[0028] The second metal layer 2 may further contain at least one element (additive element) selected from the group consisting of phosphorus (P) and tungsten (W). Of all the elements constituting the second metal layer 2, all elements other than Ni may be additive elements. The total content of the additive elements in the second metal layer 2 increases along the thickness direction D of the second metal layer 2, and the Ni content in the second metal layer 2 decreases along the thickness direction D of the second metal layer 2. In other words, the total content of the additive elements in the second metal layer 2 is lowest near the first surface S1, increases gradually or stepwise from the first surface S1 to the second surface S2, and is highest near the second surface S2. The second metal layer 2 may further contain additive elements other than P and W. When the second metal layer 2 contains additive elements other than P and W, the second metal layer 2 does not need to contain P and W.
[0029] The second metal layer 2 may be formed by electrolytic plating or electroless plating. The second metal layer 2 formed by electrolytic plating or electroless plating may be subjected to heat treatment. As shown in the examples described later, the electrolytic plating or electroless plating can reduce the Ni content in the second metal layer 2 along the thickness direction D of the second metal layer 2. For example, the control factors for the distribution of the Ni content in the second metal layer 2 may be the composition of the plating solution, the content and ratio of each raw material in the plating solution, the temperature of the plating solution, the pH of the plating solution, the current density of the first metal layer 1, and the plating time. The raw material contained in the plating solution may be, for example, a compound containing Ni and a compound containing the above-mentioned additive element. The higher the content of the Ni-containing compound in the plating solution used to form each nickel-containing layer, the higher the Ni content in each nickel-containing layer. The second metal layer 2 may be formed of a plurality of nickel-containing layers having different Ni contents by carrying out a plurality of plating processes with different control factors. That is, the Ni content in each of the multiple nickel-containing layers constituting the second metal layer 2 may be controlled so that the Ni content in the second metal layer 2 decreases along the thickness direction D of the second metal layer 2. The current density of the first metal layer during electrolytic plating may be reduced continuously or stepwise over time to form a second metal layer 2 in which the Ni content decreases along the thickness direction D.
[0030] Cu may be the main component of the first metal layer 1. The first metal layer 1 may consist only of Cu. The first metal layer 1 may consist of an alloy containing Cu. When the first metal layer 1 contains Cu, the laminate 10 can have high conductivity required for a negative electrode current collector for a lithium ion secondary battery.
[0031] The negative electrode active material contained in the negative electrode active material layer 3 may be any material that can occlude and release lithium ions, and is not particularly limited. For example, the negative electrode active material contained in the negative electrode active material layer 3 may contain silicon (Si). The negative electrode active material containing silicon is more likely to expand and contract with the charge and discharge of the lithium ion secondary battery than other negative electrode active materials. Due to the volume fluctuation of the negative electrode active material layer 3 accompanying charge and discharge, the laminate 10 (second metal layer 2) receives repeated tensile stress. However, according to the present embodiment, peeling of the second metal layer 2 from the first metal layer 1 due to the volume fluctuation of the negative electrode active material layer 3 is suppressed.
[0032] The negative electrode active material containing silicon may be a simple substance of silicon, an alloy containing silicon, or a compound containing silicon (such as an oxide or a silicate). For example, the alloy containing silicon may contain at least one element selected from the group consisting of tin (Sn), nickel (Ni), copper (Cu), iron (Fe), cobalt (Co), manganese (Mn), zinc (Zn), indium (In), silver (Ag), titanium (Ti), germanium (Ge), bismuth (Bi), antimony (Sb), and chromium (Cr). For example, the compound containing silicon may contain at least one element selected from the group consisting of boron (B), nitrogen (N), oxygen (O), and carbon (C). For example, the negative electrode active material containing silicon may be at least one compound selected from the group consisting of SiB4, SiB6, Mg2Si, Ni2Si, TiSi2, MoSi2, CoSi2, NiSi2, CaSi2, CrSi2, Cu5Si, FeSi2, MnSi2, NbSi2, TaSi2, VSi2, WSi2, ZnSi2, SiC, Si2N2, Si2N2O, SiO X (0 < X ≤ 2) and at least one compound selected from the group consisting of LiSiO. The negative electrode active material may be a fiber containing silicon (such as a nanowire) or a particle containing silicon (such as a nanoparticle). The negative electrode active material layer 3 may further contain a binder. The binder binds the negative electrode active materials to each other and binds the negative electrode active material layer 3 to the surface of the second metal layer 2.
[0033] The thickness T1 of the first metal layer 1 may be, for example, 1 μm or more and 8 μm or less. The thickness T2 of one second metal layer 2 may be, for example, 0.3 μm or more and 4 μm or less, or 1.0 μm or more and 2 μm or less. The sum of the thicknesses T2 of the multiple second metal layers 2 is T2 TOTAL and T2 TOTAL / T1 may be 0.6 or more and 1.0 or less. For example, as shown in FIG. 1, when the laminate 10 has two second metal layers 2, T2 TOTAL is the sum of the thicknesses of the two second metal layers 2. TOTAL When / T1 is 0.6 or more, peeling of the second metal layer 2 from the first metal layer 1 is easily suppressed, and the laminate 10 is likely to have a sufficiently high tensile strength. TOTAL The smaller / T1 is, the lower the cost of the raw materials for the laminate 10 (second metal layer 2). TOTAL When / T1 is 1.0 or less, peeling of the second metal layer 2 from the first metal layer 1 is easily suppressed, and a lithium ion secondary battery including the laminate 10 is likely to have a sufficiently high energy density. Even when the laminate 10 includes only one second metal layer 2, for the same reason as above, T2 / T1 may be 0.6 or more and 1.0 or less. The thickness T3 of one negative electrode active material layer 3 may be, for example, 10 μm or more and 300 μm or less. The thickness T1 of the first metal layer 1, the thickness T2 of the second metal layer 2, and the thickness T3 of the negative electrode active material layer 3 may each be uniform.
[0034] The dimensions of the first metal layer 1, the second metal layer 2, and the negative electrode active material layer 3 in the direction perpendicular to the stacking direction may be approximately the same as each other. For example, the width of the first metal layer 1, the second metal layer 2, and the negative electrode active material layer 3 in the direction perpendicular to the stacking direction may be several tens of mm or more and several hundreds of mm or less. The length of the first metal layer 1, the second metal layer 2, and the negative electrode active material layer 3 in the direction perpendicular to the stacking direction may be several tens of mm or more and several thousands of mm or less.
[0035] The present invention is not necessarily limited to the above-described embodiment. Various modifications of the present invention are possible without departing from the spirit of the present invention, and these modifications are also included in the present invention.
[0036] For example, the second metal layer may be formed by a vapor deposition process, which may be, for example, a metal-organic physical vapor deposition (MOPVD) process, such as sputtering, or a metal-organic chemical vapor deposition (MOCVD) process.
[0037] The laminate according to the present invention may be used as a heat dissipation material or an electromagnetic wave shielding material. Stress acts on the heat dissipation material or the electromagnetic wave shielding material during processing. According to the present invention, peeling of the second metal layer 2 from the first metal layer 1 during processing of the heat dissipation material or the electromagnetic wave shielding material can be suppressed. EXAMPLES
[0038] The present invention will be described in detail with reference to the following examples and comparative examples, but the present invention is not limited to the following examples.
[0039] [Pretreatment of the first metal layer] A commercially available electrolytic copper foil was used as the first metal layer. The thickness of the first metal layer was 4.5 μm. The thickness of the first metal layer was uniform. The first metal layer was immersed in an acidic degreasing solution for 1 minute to remove organic matter adhering to the surface of the first metal layer. As the degreasing solution, Thru-cup MSC-3-A manufactured by Uemura Kogyo Co., Ltd. was used. After degreasing, the first metal layer was cleaned by immersing it in pure water for 1 minute.
[0040] After cleaning, the first metal layer was immersed in dilute sulfuric acid for 1 minute to remove the native oxide film present on the surface of the first metal layer. The concentration of the dilute sulfuric acid was 10 mass %. After removing the native oxide film, the first metal layer was immersed in pure water for 1 minute to clean the first metal layer.
[0041] Using the first metal layer that had been subjected to the above pretreatment, laminates of Examples 1 to 13 and Comparative Examples 1 to 4 were produced by the following method.
[0042] Example 1 The second metal layer was formed on both surfaces of the first metal layer by the following electrolytic plating, i.e., a laminate was formed by the electrolytic plating, which was composed of the first metal layer and the second metal layer laminated on both surfaces of the first metal layer. The second metal layer in Example 1 was composed of a first nickel-containing layer L1 laminated directly on the surface of the first metal layer, a second nickel-containing layer L2 laminated directly on the first nickel-containing layer L1, and a third nickel-containing layer L3 laminated directly on the second nickel-containing layer L2. The surface of the first nickel-containing layer L1 in contact with the first metal layer corresponds to the first surface of the second metal layer.
[0043] In the electrolytic plating, the first metal layer and the other electrodes connected to a power source were immersed in a plating solution, and a current was applied to the first metal layer and the other electrodes. The plating solution contained nickel sulfate hexahydrate, sodium tungstate dihydrate, and trisodium citrate. The content of nickel sulfate hexahydrate in the plating solution was 60 g / L. The content of sodium tungstate dihydrate in the plating solution was 100 g / L. The content of trisodium citrate in the plating solution was 145 g / L. The pH of the plating solution was adjusted to 5.0. The temperature of the plating solution was adjusted to 50°C.
[0044] <Formation of first nickel-containing layer L1> The current density of the first metal layer during electrolytic plating is 5A / dm 2 The electrolytic plating was continued for 0.5 minutes, thereby forming a first nickel-containing layer L1 on the surface of the first metal layer.
[0045] <Formation of second nickel-containing layer L2> Before forming the second nickel-containing layer L2, the first metal layer on which the first nickel-containing layer L1 was formed was immersed in pure water for one minute to clean the surface of the first nickel-containing layer L1. The first metal layer on which the first nickel-containing layer L1 was formed was immersed in the plating solution together with the other electrodes. The current density of the first metal layer during electrolytic plating was set to 3 A / dm 2The electrolytic plating was continued for 0.8 minutes, thereby forming a second nickel-containing layer L2 on the surface of the first nickel-containing layer L1.
[0046] <Formation of third nickel-containing layer L3> Before forming the third nickel-containing layer L3, the first metal layer on which the second nickel-containing layer L2 was formed was immersed in pure water for one minute to clean the surface of the second nickel-containing layer L2. The first metal layer on which the second nickel-containing layer L2 was formed was immersed in the plating solution together with the other electrodes. The current density of the first metal layer during electrolytic plating was set to 2 A / dm 2 The electrolytic plating was continued for 1.3 minutes, thereby forming a third nickel-containing layer L3 on the surface of the second nickel-containing layer L2.
[0047] The laminate formed by the above plating method was washed by immersing it in pure water for 1 minute. After washing the laminate, the moisture adhering to the laminate was removed. After removing the moisture, the laminate was heat-treated at 110°C for 6 hours.
[0048] By the above method, the laminate of Example 1 was produced. In the case of Example 1, the exposed surface of the third nickel-containing layer L3 corresponds to the second surface of the second metal layer.
[0049] Example 2 In the case of Example 2, only the first nickel-containing layer L1 was formed on both surfaces of the first metal layer as the second metal layer. In the process of forming the first nickel-containing layer L1 in Example 2, the current density of the first metal layer during electrolytic plating was increased to 5 A / dm 2 from 2A / dm 2 The duration of electrolytic plating in Example 2 was adjusted so that the integrated current of the first metal layer during electrolytic plating was the same as that in Example 1.
[0050] Except for the above, the laminate of Example 2 was produced in the same manner as in Example 1. In the case of Example 2, the exposed surface of the first nickel-containing layer L1 corresponds to the second surface of the second metal layer.
[0051] Example 3 In the process of forming the first nickel-containing layer L1 in Example 3, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 0.2 minutes. In the process of forming the second nickel-containing layer L2 in Example 3, the current density of the first metal layer was 4 A / dm 2 and electrolytic plating continued for 0.4 minutes. In the process of forming the third nickel-containing layer L3 in Example 3, the current density of the first metal layer was 3 A / dm 2 and electrolytic plating continued for 0.7 minutes. In the case of Example 3, after the surface of the third nickel-containing layer L3 was washed with pure water, a fourth nickel-containing layer L4 was formed on the surface of the third nickel-containing layer L3. That is, the second metal layer in Example 3 was composed of a first nickel-containing layer L1 laminated directly on the surface of the first metal layer, a second nickel-containing layer L2 laminated directly on the first nickel-containing layer L1, a third nickel-containing layer L3 laminated directly on the second nickel-containing layer L2, and a fourth nickel-containing layer L4 laminated directly on the third nickel-containing layer L3. During the formation of the fourth nickel-containing layer L4, the current density of the first metal layer is 2 A / dm 2 and electrolytic plating continued for 1.3 minutes. Except for the above, the laminate of Example 3 was produced in the same manner as in Example 1. In the case of Example 3, the exposed surface of the fourth nickel-containing layer L4 corresponds to the second surface of the second metal layer.
[0052] Example 4 In the process of forming the first nickel-containing layer L1 in Example 4, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 0.5 min. In the process of forming the second nickel-containing layer L2 in Example 4, the current density of the first metal layer was 2 A / dm 2 and electrolytic plating continued for 5 minutes. In the case of Example 4, the third nickel-containing layer L3 was not formed. Except for the above, the laminate of Example 4 was produced in the same manner as in Example 1. In the case of Example 4, the exposed surface of the second nickel-containing layer L2 corresponds to the second surface of the second metal layer.
[0053] Example 5 In the case of Example 5, second metal layers were formed on both surfaces of the first metal layer by the following electroless plating, rather than by electrolytic plating. The second metal layers in Example 5 consisted of a first nickel-containing layer L1 laminated directly on the surface of the first metal layer, a second nickel-containing layer L2 laminated directly on the first nickel-containing layer L1, and a third nickel-containing layer L3 laminated directly on the second nickel-containing layer L2.
[0054] <Catalyst treatment> Before the formation of the first nickel-containing layer L1, a catalytic treatment was carried out on the surface of the first metal layer. In the catalytic treatment, the first metal layer was immersed in a catalytic treatment solution for one minute to attach a catalyst (palladium sulfate) to the surface of the first metal layer. The temperature of the catalytic treatment solution was adjusted to 40°C. Axmalta MNK-4-M manufactured by Uemura Kogyo Co., Ltd. was used as the catalytic treatment solution.
[0055] <Formation of first nickel-containing layer L1> In the process of forming the first nickel-containing layer L1, the first metal layer was immersed in an electroless nickel plating solution. The electroless nickel plating solution used in forming the first nickel-containing layer L1 was Top Nicoron LPH manufactured by Okuno Chemical Industries Co., Ltd. The electroless nickel plating solution contained sodium hypophosphite as a reducing agent. The temperature of the electroless nickel plating solution was adjusted to 90°C. The duration of the electroless plating was 2 minutes.
[0056] <Formation of second nickel-containing layer L2> Before forming the second nickel-containing layer L2, the first metal layer on which the first nickel-containing layer L1 was formed was immersed in pure water for 1 minute to clean the surface of the first nickel-containing layer L1. After cleaning the surface of the first nickel-containing layer L1, the surface of the first nickel-containing layer L1 was subjected to catalytic treatment by the above-mentioned method before forming the second nickel-containing layer L2. In the process of forming the second nickel-containing layer L2, the first metal layer on which the first nickel-containing layer L1 was formed was immersed in an electroless nickel plating solution. The electroless nickel plating solution used in forming the second nickel-containing layer L2 was ICP Nicoron GM manufactured by Okuno Chemical Industries Co., Ltd. The electroless nickel plating solution contained sodium hypophosphite as a reducing agent. The temperature of the electroless nickel plating solution was adjusted to 80°C. The duration of the electroless plating was 2.5 minutes.
[0057] <Formation of third nickel-containing layer L3> Before forming the third nickel-containing layer L3, the first metal layer on which the second nickel-containing layer L2 was formed was immersed in pure water for 1 minute to clean the surface of the second nickel-containing layer L2. After cleaning the surface of the second nickel-containing layer L2, the surface of the second nickel-containing layer L2 was subjected to catalytic treatment by the above-mentioned method before forming the third nickel-containing layer L3. In the process of forming the third nickel-containing layer L3, the first metal layer on which the second nickel-containing layer L2 was formed was immersed in an electroless nickel plating solution. The electroless nickel plating solution used in forming the third nickel-containing layer L3 was ICP Nicoron SOF manufactured by Okuno Chemical Industries Co., Ltd. The electroless nickel plating solution contained sodium hypophosphite as a reducing agent. The temperature of the electroless nickel plating solution was adjusted to 85°C. The duration of the electroless plating was 2.5 minutes. After the formation of the third nickel-containing layer L3, the laminate was washed by immersing the laminate in pure water for 1 minute.
[0058] By the above method, the laminate of Example 5 was produced. In the case of Example 5, the exposed surface of the third nickel-containing layer L3 corresponds to the second surface of the second metal layer.
[0059] Example 6 In the case of Example 6, the third nickel-containing layer L3 was not formed. Except for this, the laminate of Example 6 was produced in the same manner as in Example 5. In the case of Example 6, the exposed surface of the second nickel-containing layer L2 corresponds to the second surface of the second metal layer.
[0060] Example 7 Electrolytic plating of Example 7 was carried out using a plating solution having a different composition from that of Example 1. The plating solution of Example 7 contained nickel sulfate hexahydrate, nickel chloride hexahydrate, boric acid, trisodium citrate, and sodium hydrogen phosphite. The content of nickel sulfate hexahydrate in the plating solution of Example 7 was 100 g / L. The content of nickel chloride hexahydrate in the plating solution of Example 7 was 30 g / L. The content of boric acid in the plating solution of Example 7 was 30 g / L. The content of trisodium citrate in the plating solution of Example 7 was 30 g / L. The content of sodium hydrogen phosphite in the plating solution of Example 7 was 20 g / L. The pH of the plating solution of Example 7 was adjusted to 3.5. The temperature of the plating solution of Example 7 was adjusted to 60°C.
[0061] In the case of Example 7, only the first nickel-containing layer L1 was formed on both surfaces of the first metal layer as the second metal layer. In the process of forming the first nickel-containing layer L1 in Example 7, the current density of the first metal layer during electrolytic plating was increased to 4 A / dm 2 From 0.5A / dm 2 The duration of electrolytic plating in Example 7 was adjusted so that the integrated current of the first metal layer during electrolytic plating was the same as that in Example 5.
[0062] Except for the above, the laminate of Example 7 was produced in the same manner as in Example 1. In the case of Example 7, the exposed surface of the first nickel-containing layer L1 corresponds to the second surface of the second metal layer.
[0063] Example 8 The nickel content in the electroless nickel plating solution used to form the second nickel-containing layer L2 in Example 8 was greater than the nickel content in the electroless nickel plating solution used to form the second nickel-containing layer L2 in Example 5. Except for this, the laminate of Example 8 was produced in the same manner as in Example 5. In the case of Example 8, the exposed surface of the third nickel-containing layer L3 corresponds to the second surface of the second metal layer.
[0064] Example 9 The first nickel-containing layer L1 of Example 9 was formed by electrolytic plating using the following first plating solution. The content of nickel sulfate hexahydrate in the first plating solution of Example 9 was 40 g / L. The content of sodium tungstate dihydrate in the first plating solution of Example 9 was 45 g / L. The content of trisodium citrate in the first plating solution of Example 9 was 80 g / L. The pH of the first plating solution of Example 9 was adjusted to 7.0. In the process of forming the first nickel-containing layer L1 of Example 9, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 3 minutes.
[0065] The second nickel-containing layer L2 of Example 9 was formed by electrolytic plating using the following second plating solution. The content of nickel sulfate hexahydrate in the second plating solution of Example 9 was 30 g / L. The content of sodium tungstate dihydrate in the second plating solution of Example 9 was 60 g / L. The content of trisodium citrate in the second plating solution of Example 9 was 80 g / L. The pH of the second plating solution of Example 9 was adjusted to 7.0. In the process of forming the second nickel-containing layer L2 of Example 9, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 3 minutes.
[0066] In the case of Example 9, the third nickel-containing layer L3 was not formed. Except for the above, the laminate of Example 9 was produced in the same manner as in Example 1. In the case of Example 9, the exposed surface of the second nickel-containing layer L2 corresponds to the second surface of the second metal layer.
[0067] Example 10 The first nickel-containing layer L1 of Example 10 was formed by electrolytic plating using the following first plating solution. The content of nickel sulfate hexahydrate in the first plating solution of Example 10 was 60 g / L. The content of sodium tungstate dihydrate in the first plating solution of Example 10 was 30 g / L. The content of trisodium citrate in the first plating solution of Example 10 was 80 g / L. The pH of the first plating solution of Example 10 was adjusted to 7.0. In the process of forming the first nickel-containing layer L1 of Example 10, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 1 minute.
[0068] The second nickel-containing layer L2 of Example 10 was formed by electrolytic plating using the following second plating solution. The content of nickel sulfate hexahydrate in the second plating solution of Example 10 was 40 g / L. The content of sodium tungstate dihydrate in the second plating solution of Example 10 was 45 g / L. The content of trisodium citrate in the second plating solution of Example 10 was 80 g / L. The pH of the second plating solution of Example 10 was adjusted to 7.0. In the process of forming the second nickel-containing layer L2 of Example 10, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 1 minute.
[0069] The third nickel-containing layer L3 of Example 10 was formed by electrolytic plating using the following third plating solution. The content of nickel sulfate hexahydrate in the third plating solution of Example 10 was 30 g / L. The content of sodium tungstate dihydrate in the third plating solution of Example 10 was 60 g / L. The content of trisodium citrate in the third plating solution of Example 10 was 80 g / L. The pH of the third plating solution of Example 10 was adjusted to 7.0. In the process of forming the third nickel-containing layer L3 of Example 10, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 1 minute.
[0070] Except for the above, the laminate of Example 10 was produced in the same manner as in Example 1. In the case of Example 10, the exposed surface of the third nickel-containing layer L3 corresponds to the second surface of the second metal layer.
[0071] Example 11 The first nickel-containing layer L1 of Example 11 was formed by electrolytic plating using the following first plating solution. The content of nickel sulfate hexahydrate in the first plating solution of Example 11 was 70 g / L. The content of sodium tungstate dihydrate in the first plating solution of Example 11 was 15 g / L. The content of trisodium citrate in the first plating solution of Example 11 was 80 g / L. The pH of the first plating solution of Example 11 was adjusted to 7.0. In the process of forming the first nickel-containing layer L1 of Example 11, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 1.5 minutes.
[0072] The second nickel-containing layer L2 of Example 11 was formed by electrolytic plating using the following second plating solution. The content of nickel sulfate hexahydrate in the second plating solution of Example 11 was 60 g / L. The content of sodium tungstate dihydrate in the second plating solution of Example 11 was 8 g / L. The content of trisodium citrate in the second plating solution of Example 11 was 30 g / L. The pH of the second plating solution of Example 11 was adjusted to 7.0. In the process of forming the second nickel-containing layer L2 of Example 11, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 2 minutes.
[0073] In the case of Example 11, the third nickel-containing layer L3 was not formed. Except for the above, the laminate of Example 11 was produced in the same manner as in Example 1. In the case of Example 11, the exposed surface of the second nickel-containing layer L2 corresponds to the second surface of the second metal layer.
[0074] Example 12 The first nickel-containing layer L1 of Example 12 was formed by electrolytic plating using the following first plating solution. The content of nickel sulfate hexahydrate in the first plating solution of Example 12 was 70 g / L. The content of sodium tungstate dihydrate in the first plating solution of Example 12 was 8 g / L. The content of trisodium citrate in the first plating solution of Example 12 was 80 g / L. The pH of the first plating solution of Example 12 was adjusted to 7.0. In the process of forming the first nickel-containing layer L1 of Example 12, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 1 minute.
[0075] The second nickel-containing layer L2 of Example 12 was formed by electrolytic plating using the following second plating solution. The content of nickel sulfate hexahydrate in the second plating solution of Example 12 was 70 g / L. The content of sodium tungstate dihydrate in the second plating solution of Example 12 was 15 g / L. The content of trisodium citrate in the second plating solution of Example 12 was 80 g / L. The pH of the second plating solution of Example 12 was adjusted to 7.0. In the process of forming the second nickel-containing layer L2 of Example 12, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 1 minute.
[0076] The third nickel-containing layer L3 of Example 12 was formed by electrolytic plating using the following third plating solution. The content of nickel sulfate hexahydrate in the third plating solution of Example 12 was 60 g / L. The content of sodium tungstate dihydrate in the third plating solution of Example 12 was 30 g / L. The content of trisodium citrate in the third plating solution of Example 12 was 80 g / L. The pH of the third plating solution of Example 12 was adjusted to 7.0. In the process of forming the third nickel-containing layer L3 of Example 12, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 1 minute.
[0077] Except for the above, a laminate of Example 12 was produced in the same manner as in Example 1. In the case of Example 12, the exposed surface of the third nickel-containing layer L3 corresponds to the second surface of the second metal layer.
[0078] (Example 13) The first nickel-containing layer L1 of Example 13 was formed by electrolytic plating using the following first plating solution. The content of nickel sulfate hexahydrate in the first plating solution of Example 13 was 70 g / L. The content of sodium tungstate dihydrate in the first plating solution of Example 13 was 4 g / L. The content of trisodium citrate in the first plating solution of Example 13 was 80 g / L. The pH of the first plating solution of Example 13 was adjusted to 7.0. In the process of forming the first nickel-containing layer L1 of Example 13, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 1.5 minutes.
[0079] The second nickel-containing layer L2 of Example 13 was formed by electrolytic plating using the following second plating solution. The content of nickel sulfate hexahydrate in the second plating solution of Example 13 was 70 g / L. The content of sodium tungstate dihydrate in the second plating solution of Example 13 was 8 g / L. The content of trisodium citrate in the second plating solution of Example 13 was 80 g / L. The pH of the second plating solution of Example 13 was adjusted to 7.0. In the process of forming the second nickel-containing layer L2 of Example 13, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 1.5 minutes.
[0080] In the case of Example 13, the third nickel-containing layer L3 was not formed. Except for the above, the laminate of Example 13 was produced in the same manner as in Example 1. In the case of Example 13, the exposed surface of the second nickel-containing layer L2 corresponds to the second surface of the second metal layer.
[0081] Comparative Example 1 In the case of Comparative Example 1, only the first nickel-containing layer L1 was formed as the second metal layer on both surfaces of the first metal layer. Electrolytic plating of Comparative Example 1 was performed using a plating solution having a different composition from that of Example 1. The plating solution of Comparative Example 1 contained nickel sulfate hexahydrate, nickel chloride hexahydrate, and boric acid. The content of nickel sulfate hexahydrate in the plating solution of Comparative Example 1 was 240 g / L. The content of nickel chloride hexahydrate in the plating solution of Comparative Example 1 was 45 g / L. The content of boric acid in the plating solution of Comparative Example 1 was 30 g / L. The pH of the plating solution was adjusted to 4.2. The temperature of the plating solution was adjusted to 40°C. In the process of forming the first nickel-containing layer L1 in Comparative Example 1, the current density of the first metal layer during electrolytic plating was 5 A / dm 2 and electrolytic plating continued for 1.5 minutes.
[0082] Except for the above, the laminate of Comparative Example 1 was produced in the same manner as in Example 1. In the case of Comparative Example 1, the exposed surface of the first nickel-containing layer L1 corresponds to the second surface of the second metal layer.
[0083] Comparative Example 2 In the case of Comparative Example 2, only the first nickel-containing layer L1 was formed as the second metal layer on both surfaces of the first metal layer. In the case of Comparative Example 2, the current density of the first metal layer during electrolytic plating was 5 A / dm 2 The electrolytic plating was continued for 2 minutes, thereby forming a first nickel-containing layer L1 on the surface of the first metal layer.
[0084] Except for the above, the laminate of Comparative Example 2 was produced in the same manner as in Example 1. In the case of Comparative Example 2, the exposed surface of the first nickel-containing layer L1 corresponds to the second surface of the second metal layer.
[0085] Comparative Example 3 In the case of Comparative Example 3, only the first nickel-containing layer L1 was formed as the second metal layer on both surfaces of the first metal layer. The electroless nickel plating solution used in forming the first nickel-containing layer L1 in Comparative Example 3 was the same as the electroless nickel plating solution used in forming the third nickel-containing layer L3 in Example 5. In the process of forming the first nickel-containing layer L1 in Comparative Example 3, the duration of electroless plating was 7 minutes.
[0086] Except for the above, the laminate of Comparative Example 3 was produced in the same manner as in Example 5. In the case of Comparative Example 3, the exposed surface of the first nickel-containing layer L1 corresponds to the second surface of the second metal layer.
[0087] Comparative Example 4 In the process of forming the first nickel-containing layer L1 in Comparative Example 4, the current density of the first metal layer during electrolytic plating was 3 A / dm 2 and electrolytic plating continued for 0.8 minutes. In the process of forming the second nickel-containing layer L2 in Comparative Example 4, the current density of the first metal layer during electrolytic plating was 4 A / dm 2 and electrolytic plating continued for 0.6 minutes. In the process of forming the third nickel-containing layer L3 in Comparative Example 4, the current density of the first metal layer during electrolytic plating was 5 A / dm 2 The electrolytic plating was continued for 0.5 minutes.
[0088] Except for the above, the laminate of Comparative Example 4 was produced in the same manner as in Example 1. In the case of Comparative Example 4, the exposed surface of the third nickel-containing layer L3 corresponds to the second surface of the second metal layer.
[0089] [Laminate analysis] The laminates of Examples 1 to 13 and Comparative Examples 1 to 4 were analyzed by the following method.
[0090] The laminate was cut in the lamination direction (the direction perpendicular to the first surface of the second metal layer). The cross section of the laminate was observed with a scanning electron microscope (SEM). The composition of the second metal layer exposed in the cross section of the laminate was analyzed by energy dispersive X-ray spectroscopy (EDS) along the thickness direction D of the second metal layer.
[0091] It was confirmed that the second metal layers of each of Examples 1 to 13 and Comparative Examples 1 to 4 contained the constituent elements shown in Table 1 below.
[0092] The Ni content [Ni] in each nickel-containing layer constituting the second metal layer in each of Examples 1 to 13 and Comparative Examples 1 to 4 is shown in Table 1 below. L1 in Table 1 means the first nickel-containing layer. L2 in Table 1 means the second nickel-containing layer. L3 in Table 1 means the third nickel-containing layer. L4 in Table 1 means the fourth nickel-containing layer. Except for Examples 2 and 7, the Ni content [Ni] in each nickel-containing layer was approximately constant.
[0093] In the cases of Examples 2 and 7, the Ni content [Ni] in the second metal layer (first nickel-containing layer L1) continuously decreased along the thickness direction D of the second metal layer. That is, in the cases of Examples 2 and 7, the Ni content in the second metal layer was maximum near the first surface of the second metal layer and minimum near the second surface of the second metal layer. In the case of Example 2, the maximum Ni content in the second metal layer was 69 mass %, and the minimum Ni content in the second metal layer was 62 mass %. In the case of Example 7, the maximum Ni content in the second metal layer was 99 mass %, and the minimum Ni content in the second metal layer was 87 mass %.
[0094] The Δ[Ni] of each of Examples 1 to 13 and Comparative Example 4 is shown in the following Table 1. The definition of Δ[Ni] is as described above.
[0095] In all of Examples 1 to 13 and Comparative Examples 1 to 4, the thickness of each nickel-containing layer constituting the second metal layer was uniform. The thickness of each nickel-containing layer was measured in the cross section of the laminate. The thickness of each nickel-containing layer is shown in Table 1 below.
[0096] [Bending test] The following bending test according to JISC5016 was carried out using each of the laminates of Examples 1 to 13 and Comparative Examples 1 to 4. The outline of the bending test is shown in FIG.
[0097] The laminate 10 used in the bending test had a rectangular shape. The length of the long side of the laminate 10 (the length of the laminate 10 in the direction perpendicular to the lamination direction) was 150 mm. The length of the short side of the laminate 10 (the width of the laminate in the direction perpendicular to the lamination direction) was 50 mm.
[0098] A cylinder 14 harder than the laminate 10 was used in the bending test. The height of the cylinder 14 was greater than the length of the short side of the laminate 10. The radius of curvature R of the outer circumferential surface of the cylinder 14 was 5 mm.
[0099] The outer peripheral surface of the cylinder 14 was in contact with the center of the laminate 10 in the long side direction of the laminate 10 so that the height direction of the cylinder 14 was parallel to the short side of the laminate 10. The laminate 10 was folded so that the surface of the laminate 10 (the second surface of the second metal layer) was in close contact with the outer peripheral surface of the cylinder 14. One end 12 of the folded laminate 10 was fixed in a jig 13. The other end 15 of the folded laminate 10 was repeatedly moved back and forth along direction B (the long side direction of the laminate 10) for one minute. The moving distance of the end 15 was 30 mm. The cycle of the reciprocation was 150 times / min.
[0100] [Peel test] After the bending test, an adhesive tape was applied to the portion of the laminate 10 that had been in close contact with the outer peripheral surface of the cylindrical body 14 (the second surface of the second metal layer). After the adhesive tape was peeled off from the laminate 10, the total area a of the portion of the adhesive tape surface where the second metal layer was attached was measured. The peeling rate R, defined by the following mathematical formula 1, P (Unit: %) was calculated. In formula 1, A is the total surface area of the adhesive tape. As the adhesive tape, a cellophane adhesive tape specified in JIS Z 1522 was used. R P =100×a / A (1)
[0101] The results of the peeling tests for each of the above-mentioned Examples 1 to 13 and Comparative Examples 1 to 4 are shown in the following Table 1. In Table 1, A represents the peeling rate RP The B in Table 1 means that the peeling rate R P The C in Table 1 means that the peeling rate R P This means that the percentage is 10% or more.
[0102] [Table 1] [Industrial Applicability]
[0103] For example, the laminate according to one aspect of the present invention may be used as a negative electrode current collector of a lithium ion secondary battery. [Explanation of symbols]
[0104] 1...first metal layer, 2...second metal layer, 3...negative electrode active material layer, 10...laminated body (current collector), 20...negative electrode, D...thickness direction of second metal layer, S1...first surface of second metal layer, S2...second surface of second metal layer.
Claims
1. A negative electrode current collector for a lithium ion secondary battery, comprising: The negative electrode current collector comprises a laminate, The laminate comprises: a first metal layer comprising copper; a second metal layer comprising nickel and laminated directly to the first metal layer; Equipped with the first surface of the second metal layer is in contact with the first metal layer; a second surface of the second metal layer that is opposite to the first surface; a thickness direction of the second metal layer is substantially perpendicular to the first surface and extends from the first surface to the second surface; The unit of the nickel content in the second metal layer is mass %, the nickel content of the second metal layer decreases along the thickness direction; Negative electrode current collector.
2. The second metal layer further contains at least one element selected from the group consisting of phosphorus and tungsten. The negative electrode current collector according to claim 1 .
3. the second metal layer is made of a plurality of nickel-containing layers stacked in the thickness direction, The nickel content of each of the plurality of nickel-containing layers is different from each other; The negative electrode current collector according to claim 1 or 2.
4. The thickness of the first metal layer is represented as T1; The thickness of the second metal layer is designated T2; T2 / T1 is 0.6 or more and 1.0 or less; The negative electrode current collector according to any one of claims 1 to 3.
5. the nickel content of the second metal layer is highest near the first surface, decreases stepwise along the thickness direction, and is lowest near the second surface; The negative electrode current collector according to any one of claims 1 to 4.
6. the nickel content of the second metal layer is highest near the first surface, decreases continuously along the thickness direction, and is lowest near the second surface; The negative electrode current collector according to any one of claims 1 to 4.
7. The negative electrode current collector according to any one of claims 1 to 6, a negative electrode active material layer including a negative electrode active material; Equipped with the negative electrode active material layer is laminated directly on the second surface of the second metal layer; A negative electrode for lithium-ion secondary batteries.
8. The negative electrode active material contains silicon. The negative electrode according to claim 7.
Citation Information
Patent Citations
Cu-Ni functionally gradient material and preparation method thereof
CN102673040A
Negative electrode current collector for nonaqueous electrolytic solution secondary battery
JP2005197205A
JP2005‐197205A
Conductive particle, anisotropic conductive adhesive, connection structure and production method of conductive particle
JP2015170561A
Laminate
JP2018180098A